“I want to serve, but the public does not understand”—An approach to employees’ intention to stay in the Malaysian construction companies - Moshood, Taofeeq D.; Adeleke, A. Q.; Nawanir, Gusman; Sorooshian, Shahryar; Ajibike, W. A. (MDPI, 2021)
This paper explicitly clarifies an employee’s goal to voluntarily stay in his/her current employment. A large volume of research has concentrated on corporate environments on the causes of workforce turnover. Nevertheless, little was done to investigate workers’ desire to remain, which was the essential parameter in determining their stay in the construction sector. Therefore, this research was undertaken to explore the relationship between job embeddedness (off-the-job and on-the-job and the intent of staying in Malaysian construction companies with the mediating impact of continuance commitment. For the analysis, a simple random under probability sampling technique was used. Of the overall 280 samples surveyed, 243 responded and used it in the report, 86.8% of the response rate. A structural equation modeling approach was used to analyze the direct and indirect relationships as drawn by the hypotheses. This research showed that the component of the off-the-job, on-the-job embeddedness and intention to stay were substantially linked. At the same time, continuance commitment plays a full mediation between the convergence of off-the-job, on-the-job and the intention to stay. These findings suggest that construction companies in Malaysia need to consider organizational and community embeddedness relationships along with continuance commitment in the invention of programs designated to influence workers’ intention to stay on their current jobs.